Pathological complete response of initially unresectable multiple liver metastases achieved using combined peptide receptor radionuclide therapy and somatostatin analogs following pancreatic neuroendocrine tumor resection: a case report - Ryosuke Umino; Satoshi Nara; Noritoshi Kobayashi; Takahiro Mizui; Takeshi Takamoto; Daisuke Ban; Minoru Esaki; Nobuyoshi Hiraoka; Kazuaki Shimada (Surgical Case Reports, 2024)
Abstract Background Peptide receptor radionuclide therapy (PRRT) serves as a novel and effective treatment option for somatostatin receptor-positive unresectable liver metastases of pancreatic neuroendocrine tumors (PNETs). However, there are few reported cases of surgical resection for initially unresectable liver metastases of PNET that were converted to resectable after PRRT. Here we report a case where PRRT and somatostatin analogs (SSAs) led to a pathological complete response of initially unresectable multiple liver metastases following PNET resection. Case presentation A 52-year-old man underwent pylorus-preserving pancreaticoduodenectomy for PNET at age 40 and subsequent hepatectomies for resectable liver metastases at 44 and 47 years of age. At age 48, a follow-up examination revealed unresectable multiple liver metastases, and PRRT with 177Lu-DOTATATE therapy was initiated. After four cycles of PRRT, most liver metastases diminished according to imaging studies, and the remaining two hepatic lesions continued to shrink with additional lanreotide. Conversion surgery for liver metastases was successfully performed, revealing no viable tumor cells in tissue specimens. Seventeen months after surgery, imaging showed no detectable residual tumor or recurrence. We present a review of the relevant literature that highlights the significance of our findings. Conclusions This rare case highlights the pathological complete response of initially unresectable multiple liver metastases achieved by PRRT and SSAs following PNET resection, suggesting their potential as a multimodality treatment option for unresectable PNET.